Propuesta de inversión basada en el sistema de construcción liviana en seco para vivienda en el estrato medio de Bogotá (2019)
¨CLS¨ Dry Light Construction is an alternative system, relatively modern, it is the method that uses as a support a lightweight reticular structure, armed by cold rolled galvanized steel profiles, this structure is covered with plasterboard or fiber cement with insulation For walls, mezzanines, ceilings, roof bases and facades, CLS replaces wet compounds and eliminates setting times that occur in the traditional system, the dry work system offers several advantages in time, money, weight, planning, versatility, flexibility, comfort, safety, sustainability and cleanliness.